Secure Transmission of mmWave NOMA UAV-Assisted Relay System against Randomly Located Eavesdroppers. (10th October 2022) - Diao, Danyu; Wang, Buhong; Cao, Kunrui; Dong, Runze; Cheng, Tianhao
Abstract : UAV wireless communication has been regarded as a promising technology in the fifth-generation (5G) networks. In this paper, we consider the security of the mmWave NOMA UAV-assisted relay system, where a ground source transmits messages to two types of authorized users assisted by a UAV relay in the presence of multiple eavesdroppers. A practical probabilistic line-of-sight (LoS) channel model with Nakagami-m small-scale fading and three-dimensional (3D) antenna gain is established to describe the mmWave air-to-ground channel. In addition, to improve the security of the system, cooperative jamming and protected zone strategies are introduced. The analytical expressions of connection outage probability (COP), secrecy outage probability (SOP), and effective secrecy throughput (EST) under the NOMA scheme and cooperative jamming NOMA scheme are derived. Also, the asymptotic SOP and EST are analyzed to gain further insights. The theoretic analysis and simulation results show the effectiveness of the proposed schemes. As the transmitting power of the source and UAV relay increases, the SOP depends only on the location distribution and density of eavesdroppers and the ESTs under different schemes converge to the same floor.